The use of cryoablation in treating liver tumors. (January 2014) - Aghayev, Ayaz; Tatli, Servet
Abstract : Percutaneous image-guided tumor ablation techniques have been used as an alternative method for patients with unresectable liver tumors. Although all techniques avoid morbidity and mortality of major surgery and have advantage of preserving non-tumoral liver parenchyma, cryoablation currently is the only percutaneous ablation technique allowing intraprocedural monitoring because of visibility of its ablation effect with computed tomography and MRI. Cryoablation uses extremely low temperatures to induce local tissue necrosis to treat both primary and metastatic liver tumors. This article discusses the principles of liver tumor percutaneous cryoablation, including mechanisms of tissue injury, technique, equipment, image-guidance used, patient selection criteria, clinical outcome and complications as well as current trends and future goals.